First-principles study on the preferential sites of Cr in Co7W6 - Manxiu Zhao; Haidong Huang; Taotao Tang; Xiaobo Li (Materials Research Express, 2023)
The preferential sites of Cr in the μ -Co _7 W _6 phase and its influence on electronic properties were studied by first-principles calculations based on density functional theory. The calculation results of the formation energy and defect formation energy show that the stability of the system is enhanced when Cr occupies the Co site, which indicates that Cr tends to occupy the Co site of the system. By calculating the density of states, the Hamilton population of crystal orbital, the electron location function and the Bader charge distribution, the reason why Cr preferentially occupied the Co sites is further explained. This is primarily owing to the hybridization of the d-d orbitals of the Cr atom to its adjacent atoms.